Eksplorasi Pesan-Pesan Kehidupan Dalam Aqsām Al-Qur’an - Muhd, Aisyah; Siti Harbiah; Achmad Abubakar (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
Essentially, oaths are used to strengthen a statement or information so that in the Al-Qur’an it can be found that most of the oath verses used to convey important information are supernatural in nature and difficult to believe because their existence cannot be proven. However, if we examine it in more detail, there are several oath verses that do not carry magical information, but instead discuss the human condition. Departing from this, this research aims to understand the concept of oaths in the Al-Qur’an and explore the important messages regarding the human condition contained therein. The type of research used is descriptive qualitative in the form of library research with an interpretive science approach. The research results show that the aqsām of the Al-Qur’an which is used to provide confirmation in disclosing occult information also contains many life messages such as messages to appreciate the differences contained in the QS. Al-Lail, the message of gratitude contained in QS. Al-Tīn, message to make the best use of time as contained in QS. Al-Aṣr.